1995
DOI: 10.1074/jbc.270.25.15285
|View full text |Cite
|
Sign up to set email alerts
|

Role for NF-κB in the Regulation of Ferritin H by Tumor Necrosis Factor-α

Abstract: Ferritin is a ubiquitously distributed iron-binding protein that plays a key role in cellular iron homeostasis. It is composed of two subunits, termed H (heavy or heart) and L (light or liver). In fibroblasts and other cells, the cytokine tumor necrosis factor-alpha (TNF) specifically induces synthesis of the ferritin H subunit. Using nuclear run-off assays, we demonstrate that this TNF-dependent increase in ferritin H is mediated by a selective increase in ferritin H transcription. Transfection of murine fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 35 publications
2
129
0
4
Order By: Relevance
“…However, cytosolic ferritin expression goes up mainly in microglia, which could acquire iron from phagocytosis of dead and dying cells. Cytosolic ferritin mRNA expression is also known to be increased by proinflammatory cytokines or nitric oxide (Torti et al, 1988;Wei et al, 1990;Miller et al, 1991;Kwak et al, 1995;Tsuji et al, 2000;Mikhael et al, 2006). Because inflammation and increased cytokine expression have been reported in the spinal cord of SOD1 transgenic mice (Nguyen et al, 2001), this may underlie the increase of ferritin in microglia and increase their capacity to store iron.…”
Section: Discussionmentioning
confidence: 99%
“…However, cytosolic ferritin expression goes up mainly in microglia, which could acquire iron from phagocytosis of dead and dying cells. Cytosolic ferritin mRNA expression is also known to be increased by proinflammatory cytokines or nitric oxide (Torti et al, 1988;Wei et al, 1990;Miller et al, 1991;Kwak et al, 1995;Tsuji et al, 2000;Mikhael et al, 2006). Because inflammation and increased cytokine expression have been reported in the spinal cord of SOD1 transgenic mice (Nguyen et al, 2001), this may underlie the increase of ferritin in microglia and increase their capacity to store iron.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines, tumor necrosis factor α and interleukin-1β , positively regulate ferritin synthesis in various cells including mesenchimal cells, hepatocytes, and monocyte-macrophages (Miller et al 1991). Most of the stimuli related to inflammation and directed at the synthesis of ferritin seem to upregulate H-chains preferentially over L-chains, thus resulting in an increase in catalytic sites and a reduction in the availability of iron (Kwak et al 1995).…”
Section: The Uptake Utilization and Regulation Of Iron By Cellsmentioning
confidence: 99%
“…In fact, others and we demonstrated that overexpression of ferritin H is cytoprotective against oxidative stress (Epsztejn et al, 1999;Cozzi et al, 2000;Orino et al, 2001;Pham et al, 2004). Furthermore, the ferritin H gene, but not ferritin L gene, was identified as a TNF-response gene (Torti et al, 1988;Miller et al, 1991) through activation of NF-kB (Kwak et al, 1995), and very recently NF-kBmediated induction of ferritin H is an essential mediator of the antioxidant and cytoprotective activities against TNF-induced apoptosis (Pham et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin synthesis is regulated at both transcriptional and translational levels (Torti and Torti, 2002). A preferential induction of the H subunit than the L subunit of the ferritin gene was frequently observed in response to environmental and intracellular signals during inflammation (Torti et al, 1988;Miller et al, 1991;Tsuji et al, 1991;Kwak et al, 1995), and differentiation (Chou et al, 1986;Beaumont et al, 1987Beaumont et al, , 1994 in an iron-independent manner. Alterations in the subunit composition of the ferritins have a potential to alter intracellular iron balance because there are functional differences between the H and L subunits of ferritin; the ferritin heavy chain (ferritin H) subunit has ferroxidase activity that oxidizes ferrous iron to ferric iron, while the ferritin L subunit lacks the ferroxidase center but contributes to stabilization of assembled ferritin proteins (Levi et al, , 1994Santambrogio et al, 1992).…”
Section: Introductionmentioning
confidence: 99%